Controls of crystallinity and surface roughness of Cu film in partially ionized beam deposition - Koh, Seok-Keun; Kim, Ki-Hwan; Choi, Won-Kook; Jang, Hong-Gui; Yoon, Young-Soo; Han, Sung; Jung, Hyung-Jin (Materials Research Society Symposium - Proceedings, 1995)
Changes of crystallinity and surface roughness are discussed in terms of the average energy per deposited atom in the partially ionized beam(PIB) deposition. The average energy per deposited atom can be controlled by adjusting the ionization potential, Vi and acceleration potential, Va. The ion beam consists of a Cu ion beam and residual gas ion beam and residual gases as well as Cu particles that were ionized and accelerated to provide the film with energy required for film-growth. The relative contribution of residual gas ions and Cu ions to total average energy per deposited atom was varied with the ionization potential. At fixed ionization potentials of Vi=400 V and Vi=450 V, the average energy per deposited atom was varied in the range of 0 to 120 eV with acceleration potential Va, of 0 to 4 kV. The relative intensity ratio, I(111)/I(200), of the Cu films increased from 6 to 37 and the root mean square(Rms) surface roughness decreased with an increase in acceleration potential at Vi=400 V. The relative intensity ratio, I(111)/I(200), of Cu films increased up to Va=2 kV at Vi=2 kV, above which a decrease occurred, and the surface roughness of Cu films increased as a function of acceleration potential. The degree of preferred orientation was closely related with the average energy per deposited atom. The change of Rms roughness might be affected by ion flux, particle energy and preferred orientation.